Antígenos eritrocitários e aloimunização em uma coorte de pacientes portadores de anemia falciforme - Marques, Sérgio Reis (2017)
Goal: To determine the rate of alloimmunization and the frequency of erythrocytes antigens in a cohort of patients with sickle cell anemia. Methods: Were evaluated 488 patients with sickle cell disease followed up at the University Hospital of the Federal University of Sergipe, located in Aracaju, being carried out the research of irregular antibodies and erythrocyte phenotyping. Results: A mean age of 15.9, a transfusion rate among patients with sickle cell anemia to 62.9%, among those transfused 17.9% compared to irregular antibodies and 7.9% autoantibodies. The most commonly found antibody was anti-E (22% alloimmunized) followed by anti-Kell (11%). Conclusion: A prevalence of alloimmunization was found in patients with sickle cell anemia with increased risk for those with a higher number of transfusions and were not diagnosed in neonatal screening. The most commonly found antibodies were anti-E and anti-Kell